PERAN POS BANTUAN HUKUM (POSBAKUM) KOTA TANGERANG DALAM MEMBERIKAN BANTUAN HUKUM - Sugimin; Siti Ngainnur Rohmah (Melati Institute, 2022)
This thesis examines the role of Posbakumadin in Tangerang City in providing legal assistance. The first main problem of this research is the implementation of providing legal aid according to Law Number 16 of 2011 concerning Legal Aid Article 3 and the role of Posbakumadin in Tangerang City in providing legal assistance. The purpose of this research is to know and understand about the role of Posbakumadin in Tangerang City in providing legal aid. The main problem of this research is the implementation of providing legal aid according to Law Number 16 of 2011 concerning Legal Aid Article 3 and the role of Posbakumadin in Tangerang City in provide legal assistance. This research method uses a qualitative approach with a problem approach technique through interviews, observation and in-depth documentation to the Advocates of Posbakumadin Tangerang City, Secretary and Staff and parties or clients who are accompanied by the case by Posbakumadin Tangerang City at the Tangerang District Court. The results of the study indicate that the implementation of providing legal aid according to Law Number 16 of 2011 concerning Legal Aid Article 3 has existed, exists and is used for the people of Tangerang City but the benefits have not been fully felt by the community and the role of Posbakumadin in Tangerang City in providing legal assistance is to provide information. , consultation or legal advice that does not reach the stage of accompanying or representing in the courtroom, making the documents needed for applicants for Posbakum services who are unable and providing information on a list of legal aid organizations that can provide legal assistance for free (prodeo).